Gender differences in glucoregulatory responses to intense exercise - Marliss, E. B.; Kreisman, S. H.; Manzon, A.; Halter, J. B.; Vranic, M.; Nessim, S. J. (Journal of Applied Physiology, 2000)
We compared glucoregulatory responses to intense exercise (14 min at 88% maximum O2 uptake) between genders (16 men, 12 women). Analysis of covariance of maximum O2 uptake showed no gender effect, with 82% of variance due to fat-free mass (FFM). Glycemia rose comparably during exercise but was higher in women during recovery (P = 0.02). Glucose production [rate of appearance (Ra); in mg/min] increased markedly in both; stepwise multiple regression and analysis of covariance of Ra (peak and incremental area under the curve) showed no effect of gender, body weight, or FFM. Glucose uptake [rate of disappearance (Rd)] increased less than Ra and slower in women. Rd area under the curve related to FFM (P = 0.01) but not gender or body weight. Norepinephrine and epinephrine responses (13-18× baseline) were the same and correlated significantly with Ra. Exercise insulin and glucagon changes were slight, but postexercise hyperinsulinemia was greater in women (P = 0.018), along with higher Rd. Therefore, intense exercise glucoregulation is qualitatively similar between genders, with a "feed-forward" regulation of Ra (consistent with catecholamine mediation). However, women have a lesser Rd response, related to FFM. This combination leads to greater recovery-period hyperglycemia and hyperinsulinemia.